2018
DOI: 10.1016/j.jseaes.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Accreted seamounts in North Tianshan, NW China: Implications for the evolution of the Central Asian Orogenic Belt

Abstract: A B S T R A C T The Carboniferous Bayingou ophiolitic mélange is exposed in the North Tianshan accretionary complex in the southwestern part of the Central Asian Orogenic Belt (CAOB). The mélange is mainly composed of serpentinised ultramafic rocks (including harzburgite, lherzolite, pyroxenite, dunite and peridotite), pillowed and massive basalts, layered gabbros, radiolarian cherts, pelagic limestones, breccias and tuffs, and displays blockin-matrix structures. The blocks of ultramafic rocks, gabbros, basalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 109 publications
1
28
0
Order By: Relevance
“…The mafic rocks display pronounced LREE‐enriched patterns (La N /Yb N = 4.6–17.4) with no obvious Eu anomalies which are similar to that of OIB (Figure a) and do not show obvious Nb, Ta, and Ti negative anomalies in the primitive mantle‐normalized spidergram (Figure b). These features are markedly different from those of island arc volcanic rocks (Qian et al, ) but similar to those reported for Hawaii seamount basalts (Hofmann & Jochum, ), as well as the enriched basalts from Bayingou ophiolitic mélange in North Tianshan (Yang et al, ), Mayile and Darbut ophiolitic mélange in West Junggar (Yang, Li, Gu, Yang, et al, ; Yang, Li, Santosh, Gu, et al, ; Yang, Li, Santosh, Yang, et al, ). All mafic rocks plot within OIB and oceanic plateau basalts fields in La/Yb–La/Nb and Nb/Th–Zr/Nb discrimination diagrams (Figures a,b).…”
Section: Geochemistry Of the Oib‐type Rockssupporting
confidence: 71%
See 2 more Smart Citations
“…The mafic rocks display pronounced LREE‐enriched patterns (La N /Yb N = 4.6–17.4) with no obvious Eu anomalies which are similar to that of OIB (Figure a) and do not show obvious Nb, Ta, and Ti negative anomalies in the primitive mantle‐normalized spidergram (Figure b). These features are markedly different from those of island arc volcanic rocks (Qian et al, ) but similar to those reported for Hawaii seamount basalts (Hofmann & Jochum, ), as well as the enriched basalts from Bayingou ophiolitic mélange in North Tianshan (Yang et al, ), Mayile and Darbut ophiolitic mélange in West Junggar (Yang, Li, Gu, Yang, et al, ; Yang, Li, Santosh, Gu, et al, ; Yang, Li, Santosh, Yang, et al, ). All mafic rocks plot within OIB and oceanic plateau basalts fields in La/Yb–La/Nb and Nb/Th–Zr/Nb discrimination diagrams (Figures a,b).…”
Section: Geochemistry Of the Oib‐type Rockssupporting
confidence: 71%
“…Cenozoic deformation strongly overprinted the Palaeozoic structural architecture of the Tianshan orogeny (Wang et al, ). The Palaeozoic Tianshan orogen formed during southward subduction of the Palaeo‐Tianshan and Junggar oceans and the subsequent amalgamation of various microcontinents, oceanic and continental arcs, seamounts, and accretionary complexes (Charvet et al, ; Gao et al, , ; Gao, Long, et al, ; Yang, Li, Kerr, & Tong, ; Windley et al, ; Xiao et al, ). Geologically, the Tianshan Belt is divided into three tectonic units: north, central, and south Tianshan (Gao et al, ; Gao, Long, et al, ).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Overview map showing the Central Asian Orogenic Belt and adjacent cratons (Yang et al, ). (b) The tectonic geological map of the Chinese Tianshan.…”
Section: Introductionmentioning
confidence: 99%
“…Tectonically, the Chinese Western Tianshan is usually divided into three main tectonic units from north to south (Figure b), including the North Tianshan Terrane, the Yili Block–Central Tianshan, and the South Tianshan (Gao et al, ; Yang et al, ). However, the time of collision is strongly disputed.…”
Section: Introductionmentioning
confidence: 99%